HUBUNGAN PENGETAHUAN DENGAN BREASTFEEDING SELF EFFICACY IBU DALAM PEMBERIAN ASI DI WILAYAH KERJA PUSKESMAS SINGANDARU KOTA SERANG - Anita Puji Astuti (2023)
The prevalence of breastfeeding in 2017 was 61.33% and far from target. Exclusive breastfeeding is influenced by several factors including mother's knowledge, mother's employment status, mother's stress level, and family support and environmental support. The purpose of this study was to determine the relationship between knowledge and breastfeeding self-efficacy for mothers in breastfeeding in the working area of the Puskesmas Singandaru, Serang City. This study used a cross-sectional research design with a total of 105 respondents who took part in this study with toddlers aged 0-6 months who were selected using total sampling conducted in April - May 2023. Data were collected using the Breastfeeding Self Efficacy Short questionnaire. Mother's breastfeeding knowledge form and questionnaire. Data analysis used the chi-square test. Mothers with good knowledge were 49.5% and mothers with high breastfeeding self-efficacy were 64.8%. There is a significant relationship between knowledge and breastfeeding self-efficacy with Pvalue: 0.000.